"As many as possible for as long as possible" - A case study of a soccer team that fosters multiple outcomes - Erikstad, M. K.; Johansen, B. T.; Johnsen, M.; Haugen, T.; Côté, J. (The Sport Psychologist, 2021)
The personal assets framework suggests that dynamic elements of (a) personal engagement in activities, (b) quality social dynamics, and (c) appropriate settings will influence an athlete`s long-term outcomes of performance, personal development, and continued participation in sport. The aim of the present study was to conduct a case study of a Norwegian age-restricted team that was successful in promoting participation, performance, and positive development for individual participants and to investigate how the dynamic elements of activities, social dynamics, and settings have led to these long-term outcomes. The results indicated that the case is a best-practice example of successful attainment of personal development and long-term participation and performance through appropriate structure and application of the dynamic elements within the personal assets framework, including enjoyable peer-led play activities and quality practice, quality relationships with teammates and coaches, and accessto facilities.